PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) DIGITAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SDN TANAH TINGGI 09 JAKARTA PUSAT - Nurandini, Veronika Mia; Ramadhani, Sulistyani Puteri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
n this digital era, learning media or teaching materials are needed that can utilise technology with interactive activities. Based on the results of observations and preliminary studies at SDN Tanah Tinggi 09 Central Jakarta, that media or teaching materials are needed that contain experimental learning methods and practice questions that can also be done through the use of technology. Therefore, the Digital Liveworksheet (LKPD) was developed using the Dick and Carey development model which goes through 9 adjusted development steps. The development of this Digital Liveworksheet (LKPD) was also made to improve the critical thinking skills of grade 5 students. From the results of using the media or teaching materials for the Digital Liveworksheet (LKPD), it was found that there was an increase in critical thinking skills which could be seen from the results of the pre-test and post test in each trial class. Especially in the media field test, an increase value of 67.4% was found.